Les conflits au Sud-Kivu des anciens royaumes à 1996 : rôle de la femme - Njangu, A. (Bukavu: AFECEF, 2000)
"par A. Njangu, P. Birhakaheka, C. Muhigirwa, F. Chahihabwa, J. Kusinza, V. Kayowa, V. bisimwa, J.B. Muchukiwa"